Maximal and Submaximal Cardiorespiratory Responses to a Novel Graded Karate Test - Hausen, Matheus; Freire, Raul; Machado, Andréa B.; Pereira, Glauber R.; Millet, Grégoire P.; Itaborahy, Alex (Journal of sports science & medicine, 2021)
The present study aimed to propose and assess the physiological responses of a novel graded karate test. Ten male national-level karate athletes (age 26 ± 5 yrs; body mass 69.5 ± 11.6 kg; height 1.70 ± 0.09 m) performed two exercise tests (separated by 2-7 days): 1) a running-based cardiopulmonary exercise test; 2) a graded karate test. The cardiopulmonary exercise test was comprised of an individualized ramp protocol for treadmill running, and the graded karate test was comprised of a sequence of ‘kisami-gyaku-zuki” punching at a fixed frequency of a stationary target that becomes progressively distant. Cardiorespiratory responses, blood lactate concentration, and perceived exertion were measured. A verification phase was also performed in both tests to confirm the maximal physiological outcomes. The graded karate test evoked similar maximal responses to the running protocol: V̇O2 (57.4 ± 5.1 vs 58.3 ± 3.5 mL·kg-1·min-1; p = 0.53), heart rate (192 ± 6 vs 193 ± 10]beats.min-1; p = 0.62) and blood lactate (14.6 ± 3.4 vs 13.1 ± 3.0 mmol·L-1; p = 0.14) with a shorter duration (351 ± 71 vs 640 ± 9 s; p < 0.001). Additionally, the graded karate test evoked higher V̇O2 (72.6 ± 6.5 vs 64.4 ± 4.3 %V̇O2MAX; p = 0.005) and heart rate (89.4 ± 4.6 vs 77.3 ± 7.2 %HRMAX p < 0.001) at the ventilatory threshold and a higher heart rate (97.0 ± 2.4 vs 92.9 ± 2.2 %HRMAX; p = 0.02) at the respiratory compensation point. Incremental and verification phases evoked similar responses in V̇O2 and minute-ventilation during both tests. This novel displacement-based sport-specific test evoked similar maximal and higher submaximal responses, indicating a superior pathway to assess karate athletes.